Investigation of a hybrid renewable– microgeneration energy system for power and thermal generation with reduced emissions. (February 2013) - Ribberink, Hajo; Lombardi, Kathleen; Yang, Libing; Entchev, Evgueniy
A conceptual study is described into the hybridization of Stirling engine-based residential cogeneration systems with solar thermal systems. Simulation results of four hybrid system configurations applied in various locations in Canada are presented and compared to Base Case systems without solar input. Additional optimization cases are discussed. Adding solar collectors to a residential cogeneration system has a clear potential to reduce natural gas consumption and greenhouse gas emissions. The simulated cases showed a 10%–15% decrease in the consumption of natural gas, which corresponds to a greenhouse gas emission reduction of approximately 700–1200 kg/house/year (depending on configuration and location). Hybrid systems are complex and highly integrated systems. A full system optimization was therefore not possible in this study. Recommendations are given for further optimization of this type of systems.